Consumer Legal Protection Against Non-Conformity of Goods in Online Transactions on Shopee Platform Based on Law Number 8 of 1999 - David Caniago, Ribet; Nasir, Muh; Nawas, Abu (UIN Jakarta, 2026)
The rapid development of information and communication technology has significantly increased electronic commerce transactions through marketplace platforms, one of which is Shopee. However, in practice, issues frequently arise regarding the non-conformity of goods received by consumers with the descriptions, specifications, quality, or images displayed by sellers on the platform. This condition leads to consumer losses and highlights the need for adequate legal protection. This study aims to analyze the forms of legal protection available to consumers in cases of non-conforming goods in online transactions on Shopee, based on Law Number 8 of 1999 on Consumer Protection, as well as to examine the responsibilities of business actors for consumer losses. The research employs a normative juridical method with statutory and conceptual approaches. Data sources are obtained through library research, including primary, secondary, and tertiary legal materials. The results indicate that Law Number 8 of 1999 provides comprehensive legal protection for consumers, particularly through the regulation of consumer rights to obtain goods in accordance with the promised value and condition, as stipulated in Article 4, and the obligation of business actors to provide accurate, clear, and honest information as stipulated in Article 7. In cases of non-conformity, consumers are entitled to file complaints, request returns, replacements, or refunds through mechanisms provided by Shopee, as well as through dispute resolution procedures under applicable laws. Therefore, the Consumer Protection Law serves as a strong legal foundation in ensuring legal certainty, justice, and protection for consumers in online buying and selling transactions. Keywords: Consumer Protection; Non-Conformity of Goods; Online Transactions; Shopee; Law Number 8 of 1999